Das ruas para o sistema penal: "outsiders" e mídia no contexto das manifestações urbanas - FERREIRA, Tainá Ferreira e (Universidade Federal do Pará, 2018)
The fragility of the Brazilian democratic state is perceived through constant difficulties for a guarantee of fundamental rights, and this scenario has just mobilized a population to seek ways, albeit informal, to express their demands. In 2013 and 2015, in the city of São Paulo, events occurred that exemplify the phenomena of urban manifestations, not our last years, and which became a public security agenda in the mass media. Based on these findings, this paper proposes a solution carried out by means of mass communication, during the occurrence of urban protests, a risk assessment. Through the analysis of essays by Non Governmental Organizations (NGOs) and international entities, an analysis of the two criminalization processes is sought, which the subjects, understood in the light of the Touraine concept, were exposed and what role the media play in this context. Among the conclusions obtained, it is worth noting that the media, as an informal agency of the penal system, through a work that does not prioritize the plurality of sources and thus fosters the creation of stereotypes, contributes to a criminalization of the subjects involved in the analyzed events. Moreover, the existence of a criminal policy in place of a criminal policy is seen as an obstacle to the confrontation of discourses of criminal recrudescence based on the creation of enemies.